Educação na fronteira da modernização: a política educacional no Amapá (1944-1956) - Lobato, Sidney da Silva (2009)
The first Federal Territory Amapá s government started on 1944 and finished on beginning 1956. In this period, the governor Janary Gentil Nunes and his assessors filled with estadonovista ideal of creating a modern nation they made a lot of buildings and actions to get modern Amapá s society. Education was seen as a powerful means to change amapaense s popular behaviors and values by government. This optimism resulted in a depreciative vision of the local life. Incongruity behind local culture and school s regime made high rates evasion and reproving. So, the ambitious government s plans in making modern local life didn t achieve its goal